Supplemental Material for "Single-step GBLUP genetic parameter estimations and genome-wide associations for milk fatty acid profiles, interval from calving to first insemination and ketosis in Holstein cattle" - Klein, Sarah-Luisa; Justus Liebig University Giessen (My University, 2021)
The dataset includes supplementary table S1 and figures S1-S2 for the manuscript "Single-step GBLUP genetic parameter estimations and genome-wide associations for milk fatty acid profiles, interval from calving to first insemination and ketosis in Holstein cattle" accepted for publication in the Journal of Dairy Science.